Functionalized carbon nanotubes—A boon in treating brain diseases - Rajkumar Ghosh, Jagabandhu Bag, Aparna Datta, Arup Pramanick, Isa Hassan Abubakar (Journal of Applied Pharmaceutical Science, 2023)
Typical intrinsic properties of carbon nanotube (CNTs) like one-dimensional structure with very high mechanical strength, high thermal and electrical conductivity, high aspect ratio, high surface area, ability to conjugate with functional groups, and elevated surface functionalizing capacity have made it a nanostructure of choice to be manipulated for drug delivery for the past two decades. The human brain restricts movements and or entry of ions, molecules, and cells between the blood and the brain because of the presence of the blood–brain barrier. As a result, administering drug molecules of choice to the brain under disease condition become constrained. Surface functionalized CNTs can render themselves efficient as drug carriers to the neurons, for extreme conditions like Alzheimer’s disease, glioblastoma, Parkinson’s disorder, brain stroke, brain tumor, etc. This review discussed in detail the advancement achieved so far in delivering drug molecules to the brain using CNT as the carrier and related management of toxicity so that a safer dose delivery can be made.
Keywords: Carbon nanotube, brain-diseases, functionalization, blood–brain barrier, toxicity